Peran Perempuan Yang Bekerja Sebagai PRT Dalam Meningkatkan Ekonomi Keluarga di Masa Pandemi Covid-19 Di Kelurahan Kwala Bekala - Fadilah Safna Hannur; Agus Suriadi (Universitas Muhammadiyah Sumatera Utara, 2022)
This study describes the role of women who work as housemaids in Kwala Bekala Village in improving the family economy during the COVID-19 pandemic. The purpose of this study was to determine the roles and obstacles of women who work as housemaid in Kwala Bekala Village in improving their family's economy during the Covid-19 Pandemic. This type of research is classified as descriptive with a qualitative approach which aims to describe the role of women who work as housemaid in improving the family economy during the Covid-19 pandemic. This study used a snowball sampling technique, making it easier for researchers to find informants. The number of informants in this study were 3 housewives who were married and had children, and 2 additional informants who were their employers and neighbors, and 1 key informant who knew about the location of the study. The results showed that the role played by mothers who work as housemaid in improving their family's economy is to carry out daily activities related to the household and as mothers who work to help their husbands comply family needs. Their role also has a strong impact, both in terms of income and initiatives in complying the economic needs of their families.Keywords: Fishermen, Poverty, Subsistence Strategies.